It’s Not Just a Yes or No Answer: Expressions of Local Health Department Accreditation - Meyerson, Beth E.; King, Jerry; Comer, Karen; Liu, Sandra S.; Miller, Laura (Frontiers in Public Health, 2016)
The identification and exploration of moderators of health department accreditation remain limited by current dichotomous conceptualizations of pursuit. Methods: A 2015 survey measured Indiana local health department accreditation pursuit and progress; classifying respondents by progress evidence. Covariates included attitudes about the future impact of accreditation on funding and performance, health department size, geography, health outcome ranking, and quality improvement programming. Results: Four classifications of accreditation pursuit emerged and were found to have greater association with covariates than standard dichotomous measures. “Active Pursuit” was associated with formal quality improvement programming and a belief that accreditation will impact future funding and performance. “Intent Only” was associated with no quality improvement programming and no completion of accreditation prerequisites. “Discontinued” was associated with the belief that accreditation will not impact future performance. “Not Pursuing” was associated with no interest nor plan to complete prerequisites, and reported belief that accreditation will not impact future health department funding or performance. Conclusions: More granular characterizations of accreditation pursuit may improve understanding of influential factors. This measurement framework should be validated in studies of local health departments in other states.